KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI DUSUN PENEGUK, DESA BAGU, KECAMATAN PRINGGARATA, KABUPATEN LOMBOK TENGAH - Eka Sulistiyawati; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Bagu is a village in Pringgarata District, Central Lombok Regency. The study was conducted using observational methods. The study found that yard plants in Peneguk Hamlet, Bagu Village, Pringgarata District, Central Lombok Regency had an H' of 0.16, indicating moderate diversity, moderate distribution, and moderate community stability.